Bone health in women with a history of gestational diabetes or obesity. (26th December 2019) - Engberg, Elina; Koivusalo, Saila B.; Huvinen, Emilia; Viljakainen, Heli
Abstract: Introduction: Type 2 diabetes is associated with an increased risk of bone fractures. However, bone health of women with a history of gestational diabetes (GDM) has received little attention. This cross‐sectional study compares bone health between premenopausal women with and without a history of GDM, and examines factors associated with bone health in women with a history of GDM or obesity. Material and methods: We measured areal bone mineral density for total hip, lumbar spine and whole body, and total body fat percentage (fat%) with dual‐energy X‐ray absorptiometry in 224 women. In addition, we measured bone characteristics of radius and tibia with peripheral quantitative computed tomography. Results: When compared with women without a history of GDM (mean age 39 years [SD 5], body mass index [BMI] 35 kg/m 2 [SD 6], fat% 48 [SD 7]), women with a history of GDM (age 41 years [SD 4], BMI 31 kg/m 2 [SD 7], fat% 43 [SD 10]) had lower hip and whole body bone mineral densities, and inferior tibia outcomes. However, the differences in bone characteristics disappeared after controlling for age, height, BMI and fat%. After controlling for age, height, BMI and smoking, physical activity and healthier diet were positively associated with bone outcomes, whereas fat%, HbA1c and screen time were negatively associated with bone outcomes. Particularly, fat% showed independent negative associations with whole body bone mineral density and several tibia and radius characteristics. Conclusions: Fat% is associated with adverse bone health, independently of BMI, in women with a history of GDM or obesity. Promoting healthy lifestyle and reducing fat% in high‐risk women could improve bone health and prevent future fractures.